The Impact of Reproduction Health Education Using Peer Mentoring Method Towards the Knowledge Level of Patients with Sexuality Transmitted Infection - Yanuar Eka Pujiastutik; Putri Kristyaningsih (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2021)
Sexuality transmitted infections are often also reffered to as veneral diseases. The spread can be from blood, sperm, or can also be transmitted from mother to fetus during pregnancy and birth, and through the blood and body tissues. In addition, spread can also without sexual intercourse, it can be from the use of syringes repeatedly or alternately, among people, as well as the risk of transmitting infection. The aim of this study was to determine the influence of reproduction health education using peer mentoring method towards the knowledge level of patients with sexuality transmitted infection. The study used one group pretest-posttest design. The data was collected by using a questionnaire. The respondent was selected by using total sampling technique and 27 respondents were obtained. The data was analyzed by using the Wilcoxon test. The result of the  value = 0,000, which meant  value < α (α = 0.05) there was an effect of reproduction health education using peer mentoring method towards the knowledge level of patients with sexuality transmitted infection. For researchers, next expected can be used as information to developed a method of information in other research.